Searching the chemical content of drug sibutramin hydrochloride in herbal slimming products - Wulandari, Rizkiyanti; Guntarti, Any (Journal of Halal Science and Research, 2021)
Sibutramine hydrochloride as an additive in herbal slimming products is prohibited by the Ministry of Health in accordance with the Regulation of the Minister of Health of the Republic of Indonesia number 007 of 2012 concerning Registration of Traditional Medicines. The purpose of this review is to determine the content, the highest concentration value, the identification method and the distribution area of ​​herbal slimming products containing sibutramine hydrochloride. The method used is a traditional systematic review with inclusion criteria in the form of the year of publication of the journal with a period of the last 10 years, which uses both English and Indonesian, full text, articles that contain methods and methods of identifying sibutramine hydrochloride, and articles that list the number of positive samples. contains sibutramine hydrochloride and contains levels of sibutramine hydrochloride in herbal slimming products, the article lists the research location or the location of the herbal product sampling. The presentation of data from the results of the review in descriptive form includes the percentage of products containing sibutramine hydrochloride and the highest content of sibutramine hydrochloride. The results of the article review, herbal slimming products from different research locations contain sibutramine hydrochloride by 52.17% (36). Sibutramine hydrochloride analysis methods include TLC- Densitometry, UV-Vis Spectrophotometry, HPLC, and GC-MS. The herbal slimming product with the highest concentration comes from the city of Depok with a concentration of 26.24 mg/pill, China with a concentration of 78 mg/capsule.